Survei Tingkat Kebugaran Jasmani Atlet Bulutangkis PB. Talenta Kebumen Kelompok Usia 9-12 Tahun: Penelitian - Mokhamad Parmadi; Muhammad Haidar Aljariyyi (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Physical fitness includes strength, endurance, speed, agility, and flexibility that contribute to the performance of athletes on the field. The purpose of this study was to determine the level of Physical Fitness of Badminton Athletes PB. Talenta Kebumen Age Group 9-12 Years. This study is a quantitative descriptive study with a percentage. The instruments used in this study were test instruments, including agility tests (40-meter run), muscle strength (Pull Up), flexibility (sit up), balance (vertical jump) and endurance (600-meter run). The test results showed that players who were categorized as very good or got a score of 5 were 8%. categorized as good or got a score of 4 were 58%. categorized as moderate or got a score of 3 were 29%. categorized as less or got a score of 2 were 5%. There were no students at all who were categorized as very less or got a score of 1. There are several factors that influence the physical fitness of players, including environmental factors, different individual characteristics, different player developments, training intensity and player motivation.